Regeneration of degraded periodontal tissues using enamel matrix derivative - Dr. MD Riasat HasanI; Prof. Takashi Saito (Elsevier, 2023)
Aim or Purpose: Ankylosiscan occur when periodontal tissue is not preserved properly after avulsion. According to our previous research, milk commonly recommended for tooth storage caused PDL disturbance and ankylosis. Emdogain (EMD) promotes regeneration of periodontal tissues. The purpose of the present study is to observe the effects of EMD on the periodontal tissue after immersing the tooth in milk. Materials and Methods: Five week rats' maxillary first molar teeth were extracted under general anesthesia. Extracted teeth were immersed in milk for one hour. After that, teeth were transplanted into an abdominal pocket (control group). For the experimental group, EMD were applied to the root surface of the tooth after immersion in milk for one hour. Two weeks after transplantation, rats were fixed and the teeth were carefully excised with the surrounding tissue. Immunohistochemistry & histology were performed. Results: The experimental group had more bone formation than the control group. In case of the control group, rough surface was observed in the cementum area and ankylosis was observed. On the other hand, in the experimental group, no ankylosis or rough surface in cementum area was observed. Many cathepsin K positive cells were observed in control group around the alveolar bone and cementum area. More CD68 positive cells were also detected in the control group than the experimental group. Conclusions: The present study demonstrated that, EMD has potential to help in regeneration and reconstruction of periodontal tissue in transplantation of the damage tooth.